1998
DOI: 10.1111/j.1469-7793.1998.183bo.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Kv3.1 potassium channel to high‐frequency firing in mouse auditory neurones

Abstract: Using a combination of patch‐clamp, in situ hybridization and computer simulation techniques, we have analysed the contribution of potassium channels to the ability of a subset of mouse auditory neurones to fire at high frequencies. Voltage‐clamp recordings from the principal neurones of the medial nucleus of the trapezoid body (MNTB) revealed a low‐threshold dendrotoxin (DTX)‐sensitive current (ILT) and a high‐threshold DTX‐insensitive current (IHT). I HT displayed rapid activation and deactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
404
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 341 publications
(421 citation statements)
references
References 37 publications
15
404
1
1
Order By: Relevance
“…Voltage sensitive K þ conductances determine the response properties of auditory neurons, and each cell type exhibits a distinct complement of outward K þ currents [3,67,77,123]. At least two K þ conductances underlie phase locked responses in auditory neurons: a low and a high threshold conductance [11,67,90,91,120].…”
Section: Postsynaptic Specializations For Encoding Temporal Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Voltage sensitive K þ conductances determine the response properties of auditory neurons, and each cell type exhibits a distinct complement of outward K þ currents [3,67,77,123]. At least two K þ conductances underlie phase locked responses in auditory neurons: a low and a high threshold conductance [11,67,90,91,120].…”
Section: Postsynaptic Specializations For Encoding Temporal Informationmentioning
confidence: 99%
“…This has the effect of minimizing Na þ channel inactivation, allowing cells to reach firing threshold sooner and facilitating high frequency firing. Elimination of the Kv3.1 gene in mice results in the loss of a high-threshold component of potassium current and failure of the neurons to follow high-frequency stimulation [65,120]. Brief action potentials also reduce the amount of neurotransmitter released [99].…”
Section: Postsynaptic Specializations For Encoding Temporal Informationmentioning
confidence: 99%
“…Such cells lock their action potentials precisely to the phase of auditory stimuli at frequencies of up to 2000 -4000 Hz or to rapid fluctuations in the amplitude of higher-frequencies sounds (Joris and Yin, 1995;Joris, 1996). At those frequencies at which an action potential cannot be generated to every single stimulus, their firing pattern is characterized by alternating action potentials and failures of action potential generation (Banks and Smith, 1992;Brew and Forsythe, 1995;Wang et al, 1998). For example, in response to a 600 Hz stimulus, an MNTB neuron may fire at 300 Hz, locking its action potentials to every other stimulus (Wang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…We therefore tested whether these channels contribute to the net K ϩ current in stellate cells. A low concentration of TEA is known to block preferentially a subset of K ϩ channels, including Kv3 and BK channels (Rudy and McBain 2001;Wang et al 1998). We found that bath application of 1 mM TEA reduced the outward transient current at 0 mV by 53.2 Ϯ 1.8% and the noninactivating current by 42.8 Ϯ 6.2% (n ϭ 4; P Ͻ 0.05; Fig.…”
Section: Cerebellar Stellate Cells Express Large-conductance Ca 2ϩmentioning
confidence: 73%
“…These channels display a characteristic high activation threshold and generate noninactivating currents, which accelerate the repolarization of APs. These properties reduce the AP duration and allow neurons to fire APs at high frequency (Salkoff et al 2006;Wang et al 1998). One intriguing possibility is that the brief duration of such APs suppresses the expression of GluR2 subunits in these neurons.…”
mentioning
confidence: 99%